Kedudukan Kearifan Lokal dalam Penataan Tata Ruang Kota di Pemerintahan Daerah - Muhammad Islahuddin; Maulana Muhammadinil Mukhtar (Lembaga Yasin AlSys, 2025)
Local wisdom represents an embodiment of traditional knowledge articulated in values, norms, and practices understood by communities in interaction with their natural environment, including hukum kearifan lokal (local wisdom law), which has developed and been practiced across generations within particular communities. This study aims to examine the position of local wisdom within urban spatial planning at the regional government level. A qualitative approach was employed using library research, with documentation techniques as the primary means of data collection, followed by descriptive analysis. The findings show that realizing a substantive role for local wisdom in urban spatial planning within regional governments requires planned and continuous guidance by local authorities involving various community elements, such as customary leaders, religious figures, and environmental advocates. Through the accommodation of local wisdom as a community asset in spatial planning policies and practices, implemented collaboratively by regional governments, indigenous communities, and customary leaders, local wisdom can be more substantively integrated into urban spatial management. These findings imply the need to strengthen the role of regional governments in institutionalizing local wisdom as a moral, social, and ecological foundation for sustainable urban spatial planning policies.